KERALA Kidney Trade Ambiguous Response of Medical Community - K M SEETHI (Economic and Political Weekly December 7, 2002, 2002)
The fact that the Kerala chapter of the Indian Medical Association chose to gloss over the many irregularities in the kidney trade controversy and held the medical community and the hospitals involved to be blameless, only throws into glaring focus the state's dereliction of its duty in implementing the relevant law meant to ensure ethical practice.